2012
DOI: 10.1111/j.1095-8339.2012.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

The systematic significance of bark structure in southern African genera of tribe Heteromorpheae (Apiaceae)

Abstract: The bark anatomy of five southern African genera of tribe Heteromorpheae (Apiaceae) has been investigated: Anginon (eight species), Glia (one species), Heteromorpha (two species), Polemannia (two species) and Dracosciadium (one species). They are all similar to other members of the order Apiales and share with them the presence of secretory canals in both the cortex and secondary phloem, the presence of two types of axial parenchyma and the absence of fibres in the secondary phloem. The bark of Heteromorpheae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…For example, chloroplasts have been recorded in the secondary xylem rays or pith of small diameter stems at depths of 1500–5000 μm [ 6 , 34 , 42 , 43 , 44 , 46 , 48 , 49 ]. Far fewer studies have been made of larger diameter material ( Table 1 ), with most studies indicating that the chloroplasts were in a thin band, usually 100–350 μm in depth [ 14 , 39 , 41 , 45 , 50 ]. Pilarski and Tokarz [ 17 ] investigated chloroplast distribution in both small (7 mm) and large (60 cm) diameter stems of Fagus sylvatica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chloroplasts have been recorded in the secondary xylem rays or pith of small diameter stems at depths of 1500–5000 μm [ 6 , 34 , 42 , 43 , 44 , 46 , 48 , 49 ]. Far fewer studies have been made of larger diameter material ( Table 1 ), with most studies indicating that the chloroplasts were in a thin band, usually 100–350 μm in depth [ 14 , 39 , 41 , 45 , 50 ]. Pilarski and Tokarz [ 17 ] investigated chloroplast distribution in both small (7 mm) and large (60 cm) diameter stems of Fagus sylvatica .…”
Section: Discussionmentioning
confidence: 99%
“…As an example, their data indicates that about 10 species had photosynthetic bark with a dead bark thickness of >1 mm, while about 13 species had non-photosynthetic bark with an outer bark thickness of <1 mm. Other authors have noted chlorenchyma below a 1000 μm thick phellem [ 45 ] and below a 10 mm thick rhytidome [ 66 ]. In a study of relatively small diameter stems (6–13 mm) of 13 mangrove species, Schmitz et al [ 46 ] found that xylary chlorophyll fluorescence and bark thickness (full bark thickness, not just phellem thickness) were not “strictly related” (p. 42 [ 46 ]).…”
Section: Discussionmentioning
confidence: 99%
“…All vegetables and medicinal species in Apiaceae have effective secretory systems involving different organs, including roots, stems, leaves, flowers, and fruit [ 103 105 ]. According to previous studies, the biologically active compounds of Apiaceae plants can be divided into two groups: nutrients and nutraceuticals [ 106 ].…”
Section: Apiaceae Originmentioning
confidence: 99%
“…This may be partly because unlike for anatomy, a terminology proposed for description of the bark morphology has not been commonly accepted ( Trockenbrodt 1990 ; Junikka 1994 ). Among the few articles on the interdependence between the bark macroscopic appearance and microscopic structure ( Chattaway 1953 , 1955 ; Kotina et al 2012 , 2017 ; 2018 ; Kopanina et al 2022 ), Whitmore’s studies of Dipterocarpaceae are probably the most important ( 1962a , 1962b ; 1962c ). He recognized seven bark types based on the features of the bark surface, sloughing modes, patterns of periderm formation, presence of expansion tissue, and structural traits.…”
Section: Introductionmentioning
confidence: 99%